2021
DOI: 10.1017/s1041610221000132
|View full text |Cite
|
Sign up to set email alerts
|

Depression, childhood trauma, and physical activity in older Indigenous Australians

Abstract: Objectives: Indigenous Australians experience higher levels of psychological distress compared to the general population. Physical activity is a culturally acceptable approach, associated with reduction of depressive symptoms. The protective properties of physical activity for depressive symptoms are yet to be evaluated in older Indigenous Australians. Design: A two-phase study design comprised of a qualitative thematic analysis following a quantitative regression and moderation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Caring for grandchildren was largely considered a source of positivity, which was described in terms of love, endearment, satisfaction, 'feeling good' 8,10,38 and an important cultural value. 37,46 Grandparenting was mostly described as leading to heightened respect among younger family and community members. 33,34 However, participants in four articles 8,35,38,40 expressed the need for respect and reciprocal care, which they described as lacking among younger family members.…”
Section: Grandparentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Caring for grandchildren was largely considered a source of positivity, which was described in terms of love, endearment, satisfaction, 'feeling good' 8,10,38 and an important cultural value. 37,46 Grandparenting was mostly described as leading to heightened respect among younger family and community members. 33,34 However, participants in four articles 8,35,38,40 expressed the need for respect and reciprocal care, which they described as lacking among younger family members.…”
Section: Grandparentingmentioning
confidence: 99%
“…'Healthy' ageing was perceived as acceptance of the ageing process, taking care of yourself (eg stopping smoking or drinking) 40 and being aligned with 'traditional' ways of life, as well as being able to have the physical and mental ability to pass on cultural values and knowledge. 8,9,46 Spiritual wellness was identified as being intertwined with physical wellness. 38 Returning to one's Country in old age was also seen as a protective factor against the harmful impact of racism experienced in towns, 7 and marginalisation in aged care spaces.…”
Section: Grandparentingmentioning
confidence: 99%
“…To date, little quantitative research relating to Aboriginal and Torres Strait Islander people has measured participation in the unique sociocultural contexts for aging. Instead, quantitative research has tended to report on the individual and societal burdens of aging, with a focus on the characteristics and prevalence of individual physical and biological dimensions such as dementia and cognitive impairment ( Derrig et al, 2020 ; Hocking et al, 2019 ; Lavrencic et al, 2019 ; Radford et al, 2017 ; Russell et al, 2021 ; Smith et al, 2008 ), disability and frailty ( Gubhaju et al, 2015 ; Hyde et al, 2016 , 2019 ; Lo Giudice et al, 2012 ; Lukaszyk et al, 2018 ; Wong et al, 2013 ), incontinence ( Lo Giudice et al, 2012 ; Smith et al, 2019 ), chronic disease ( McKercher et al, 2014 ; McNamara et al, 2014 ; Toelle et al, 2013 ), psychological distress ( Almeida et al, 2014 ; Mate et al, 2020 ; Rowland et al, 2021 ; Shen et al, 2018 ; Temple, Kelaher, et al, 2020 ), smoking ( Thurber et al, 2021 ), and the broader demographics of population aging ( Lo Giudice et al, 2012 ; Temple, Wilson, et al, 2020 ). Although there is increasing research that reports on narrowly defined aspects of Aboriginal sociocultural livelihoods including studies that describe racism ( Temple et al, 2019 ; Temple, Kelaher, et al, 2020 ), access to aged care and health services ( Larke et al, 2020 ), medications and vaccine equity ( Dyda et al, 2019 ; Page et al, 2019 ), the role of Aboriginal people as grandparents ( Gibberd et al, 2020 ), childhood adversity and stress ( Radford et al, 2017 ), and self-reported good health ( Lavrencic et al, 2020 ), there remains a gap in quantitative data contributing to a comprehensive picture of the sociocultural lives of older Aboriginal and Torres Strait Islander older people.…”
mentioning
confidence: 99%
“…As noted above and by authors, SDoH are a significant contributor to exposures and health outcomes among Indigenous populations. Indeed, Aboriginal Australians, the population included in "Depression, Child Trauma, and Physical Activity in Older Indigenous Australians" (Rowland et al, 2021) suffer from the greatest social disadvantage and poorest health outcomes among developed nations (Hill et al, 2007). Lifetime experiences of social disadvantage significantly contribute to poor mental health outcomes in this population later in life (Arkles et al, 2010).…”
mentioning
confidence: 99%